(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2002)
Heidegger believed that only through phenomenology is ontology possible. Indeed, he showed how this was possible in Being and Time (Heidegger 1995) offering, amongst other examples, an exploration of the use of a hammer. In this paper the author has chosen to look at her own personal experience on the golf course to gain a detailed understand of the phenomenon of playing golf badly; the objective was firstly, to understand Heidegger’s philosophy in greater depth and; secondly, to provide further insight into her therapeutic work with clients.